Dietary Fiber and WHO Food Categories Extension for the Food-Pics_Extended Database - Medawar, Evelyn; Thieleking, Ronja; Witte, A. Veronica (Frontiers in Psychology, 2022)
Well characterized databases used for experimental purposes with extensive meta-data are essential for conducting meaningful and comparable studies. The Food-pics_extendeded database (Blechert et al. 2019) is one example for a widely used food stimulus database (original publication Blechert et al. 2014: 285 citations, and 2019: 32 citations). Indeed, meta-data on low level and high level image characteristics is broad, yet fiber ratings are not included, limiting its use in diet-related studies. Therefore, we developed fiber ratings per item (n = 562 stimuli), based on mean values of four non-expert raters. Ratings show good reliability (ICC = 0.77) and meaningful ranges per food type (mean fiber per 100g by food type minbeverages = 0.04 ± 0.04 g and maxReady-to-eat savories = 4.49 ± 1.58). The newly provided fiber ratings enrich the already valuable database and extend it by an important nutrient value for human and planetary health.